Mechanical Properties of MIG Joints for Dissimilar Aluminum Alloys - Nasser, Nawres Jabar (Al-Khwarizmi Engineering Journal, 2017)
The research aims to investigate the effects of GMAW or MIG welding process on the mechanical properties of dissimilar aluminum alloys 2024-T351 and AA 6061- T651. A series of experimental techniques have been conducted to evaluate mechanical properties of the alloys, by carrying out hardness, tensile and bending tests for welded and un-welded specimens. Metal inert gas (MIG) has been carried out on sheet metal using ER- 4043(AlSi5) as a filler metal and argon as shielded gas. The welded joints were tested by X-ray radiography and Faulty pieces were excluded. Welding joints without defects are subjected to heat treatment including heating the joints in furnace to 170 °C for half an hour then air cooling to relief welding stress. Tensile test was implemented for all specimens which prepared in the dimensions according to ASTM 17500 by using Testing machine smart series with preload value 100 kN. Vickers hardness test and microstructure examination were made, the last test was bending test which implemented on the welded and un welded specimens which machined into standard test specimen dimensions. Results of mechanical properties Using MIG welding process appear a general decay compared with un welded and in the dissimilar joint comparing with parent metal that is due to the microstructure change during the welding process. The location of the failure for welded specimens after all mechanical test was found predominantly along the heat affected zone ( HAZ ).but Unwedded specimens were failed near the center line of the specimen.